2002
DOI: 10.4049/jimmunol.168.6.3050
|View full text |Cite
|
Sign up to set email alerts
|

A 320-Kilobase Artificial Chromosome Encoding the Human HLA DR3-DQ2 MHC Haplotype Confers HLA Restriction in Transgenic Mice

Abstract: MHC class II haplotypes control the specificity of Th immune responses and susceptibility to many autoimmune diseases. Understanding the role of HLA class II haplotypes in immunity is hampered by the lack of animal models expressing these genes as authentic cis-haplotypes. In this study we describe transgenic expression of the autoimmune prone HLA DR3-DQ2 haplotype from a yeast artificial chromosome (YAC) containing an intact ∼320-kb region from HLA DRA to DQB2. In YAC-transgenic mice HLA DR and DQ gene produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 60 publications
(53 reference statements)
4
22
0
Order By: Relevance
“…These mice demonstrate cell-specific regulation of the HLA-DR3 and DQ2 gene products, with fully functional CD4 ϩ and CD8 ϩ T cells (15). In the present study, we have bred mice with the HLA-DR3-DQ2 transgene to a complete class II knockout background (MHCII ⌬/⌬ ) (16), introduced human CD4 (hCD4) (17), and also generated a HLA-DQ2-restricted, gliadin-specific CD4 ϩ TCR Tg mouse to examine the pathological effect of dietary gluten on these mice.…”
Section: Cd4mentioning
confidence: 99%
See 2 more Smart Citations
“…These mice demonstrate cell-specific regulation of the HLA-DR3 and DQ2 gene products, with fully functional CD4 ϩ and CD8 ϩ T cells (15). In the present study, we have bred mice with the HLA-DR3-DQ2 transgene to a complete class II knockout background (MHCII ⌬/⌬ ) (16), introduced human CD4 (hCD4) (17), and also generated a HLA-DQ2-restricted, gliadin-specific CD4 ϩ TCR Tg mouse to examine the pathological effect of dietary gluten on these mice.…”
Section: Cd4mentioning
confidence: 99%
“…Our laboratory has previously generated Tg mice that express the HLA-DR3-DQ2 haplotype (spanning HLA-DRA to DQB2) on a partial murine class II knockout background (A␤ o/o ) (15). These mice demonstrate cell-specific regulation of the HLA-DR3 and DQ2 gene products, with fully functional CD4 ϩ and CD8 ϩ T cells (15).…”
Section: Cd4mentioning
confidence: 99%
See 1 more Smart Citation
“…Production and characterization of C57BL/6 mice homozygous or heterozygous for the HLA-DRB1*0301;-DRB3*0101;DRA1*0101;DQB1*0201;DQA1*0501 transgene haplotype and lacking endogenous class II I-A MHC molecules (DR3/DQ2 ϩ A␤ 0/0 ) have been described previously (23). Mice were maintained at the University of Melbourne Microbiology and Immunology Department animal facility.…”
Section: Methodsmentioning
confidence: 99%
“…Computer analysis was performed using the SYFPEITHI (34) and ProPred (35) programs to find similarities between the hLa epitope sequences and putative DR3 binding motifs. Probable DRB1*0301 binding registers for each of the DR3-restricted epitopes uncovered in this study were identified ( Figure 4A), indicating that the most conserved residue is the p4 position, consisting of an aspartic acid (hLa [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] , hLa 55-72 , hLa 151-168 , hLa 211-228 , hLa [241][242][243][244][245][246][247][248][249][250][251][252][253][254][255][256][257][258] , and hLa 313-330 ) or conservatively substituted glutamic acid (hLa [46][47][48][49][50][51][52][53][54] ), in 7 of 7 epitopes, followed by p1 (in 5 of 7 epitopes), p6 (in 4 of 7 epitopes), and p9 (in 3 of 7 epitopes).…”
Section: Enhancement Of the Reactivity Of A Weak Epitope In Dr3/dq2mentioning
confidence: 99%